PTH-024 Risk factors for bleeding during endoscopic resection for visible lesions in barrett's oeosphagus. (8th June 2018) - Clough, Jennifer; Zeki, Sebastian; DeMartino, Sabina; Dunn, Jason
Abstract : Introduction: Endoscopic resection (ER) is the preferred initial treatment for early cancer and dyplasia with visible lesions arising in Barrett's oesophagus (BE). An intra-procedural bleeding risk of 10% is typically quoted, with most controlled by endoscopic intervention. There is little data on risk factors for bleeding during oesophageal piecemeal ER. Studies on colonic polypectomy have shown older age and the presence of depressed lesions are associated with increased bleeding risk. Previous studies on gastric ESD have shown lesion size was the main risk factor. We sought to identify variables associated with an increased risk of bleeding. Methods: Data were collected retrospectively for patients who had undergone ER for BE at a tertiary endotherapy centre between November 2012 – October 2017. Age, anticoagulant use, Paris classification of the lesion, number of ER specimens resected, and histology of the resected tissue were recorded. From 2015 an e-noting system was used to collect blood pressure readings pre, during and post procedure, and the highest mean arterial pressure (MAP) was calculated. Bleeding was classified as mild (controlled by snare tip), moderate (controlled by coagulation graspers/clips), or severe (necessitating admission). Patients who had a moderate or severe bleed were grouped for comparison. Results: A total of 212 EMR procedures were performed in the study period. 144 were used for analysis as blood pressure recordings were available. Mean age was 71, and 76.4% were male. 28 patients bled during the procedure (19.4%), of which two had a bleed requiring admission (1.4%). There was no difference between the MAP in patients who bled during the procedure and those who did not. The mean number of ER specimens resected in total was 2.7 (range 1–12), with a greater number of resections in patients who suffered a moderate-severe bleed (3.4 vs 2.6, p=0.034). Both depressed lesions (Paris III) and pedunculated lesions (Paris Ip) conferred an increased risk of bleeding (p=0.002 and 0.011 respectively). Oesophageal cancers with a stage greater than T1b were associated with an increased bleeding risk (p=0.004). Conclusions: In this study, bleeding risk was associated with the area of the ER, with a greater risk when more ER specimens were resected. Paris type Ip and III lesions conferred an increased risk of bleeding, as did resection of an oesophageal cancer with a stage greater than T1b. This may reflect increased angiogenesis associated with lymphovascular invasion. Age, sex, anticoagulant use and intra-procedural MAP made no difference to the risk of bleeding. Importantly all bleeds were controlled by endoscopic measures and mortality was zero. In Conclusion, in patients where a wide field ER is anticipated, caution with regards to bleeding and appropriate planning for cessation of haemorrhage with endoscopic techniques should be exercised.